Aprovechamiento de residuos generados en procesos agroindustriales en la industria mezcalera (2023)
The objective of the present investigation is to analyze the physicochemical properties of the ashy agave bagasse, to carry out different hydrolysis methods such as acid hydrolysis, enzymatic hydrolysis and acid-enzymatic hydrolysis, with the purpose of analyzing which of the hydrolysis carried out produces the greatest amount of fermentable carbohydrates. After this, carry out a fermentation in order to obtain anhydrous ethanol and design a pilot plant for the production of this substance. The hydrolyses were carried out consecutively, the first being the acid hydrolysis which was carried out through digestions in three different conditions using diluted hydrochloric acid at pH 2, pH 3 and pH 4 in reaction times of 15, 30 and 40 minutes. , at a constant temperature of 80 °C and a 1:15% w/v ratio, resulting in a final concentration of 13.03 g/L in the condition of pH 3 and 30 min. The enzymatic hydrolysis was carried out using cellulase enzymes at different concentrations, a constant temperature of 50 °C, a bagasse enzyme ratio of 1:10, 1:5 and 1:1% w/v, and a time of 24-hour reaction resulting in greater carbohydrate production with the enzyme bagasse ratio of 1:5, obtaining a sugar production of 8.46 g/L.